Glucose and insulin levels' linkages with breast cancer factors - Mahashweta Das; Ishita Saha; Prasenjit Sinha; Sunit Kumar Medda; Rabindra Nath Das (Global Journal of Obesity, Diabetes and Metabolic Syndrome - Peertechz Publications, 2022)
Serum lipid and  glucose metabolisms are considered as the intermediary mechanisms for connecting obesity and Breast Cancer (BC). The article aims to identify the linkages between diabetes biochemical factors such as glucose & insulin and BC biochemical factors such as Monocyte Chemoattractant Protein-1 (MCP-1), adiponectin, Homeostasis Model Assessment score Insulin Resistance (HOMA-IR), resistin, leptin. These objectives can be focused on  the two separate statistical models of glucose & insulin based on the remaining factors. From the mean model of glucose, it is observed that mean glucose level is directly linked with BC women (P= 0.023), leptin (P<0.001), HOMA-IR (P<0.001), while it is inversely linked with the interaction effects between HOMA-IR & leptin (i.e., HOMA-IR*leptin (P<0.001)) and adiponectin & leptin (i.e., adiponectin* leptin (P= 0.088)). Similarly, from the mean model of insulin, it is observed that mean insulin level is directly linked with HOMA-IR (P<0.001), leptin (P<0.001), and the interaction effects Age*MCP-1 (P= 0.091), glucose*adiponectin (P= 0.043), glucose*resistin (P<0.001), MCP-1*HOMA-IR (P<0.001), while it is reciprocally linked with MCP-1 (P= 0.026), resistin (P<0.001), adiponectin (P= 0.078), HOMA-IR*body mass index (BMI) (P<0.001), glucose*HOMA-IR (P<0.001), leptin*adiponectin (P= 0.071). There are more linkages of the variances of insulin and glucose with the BC biochemical factors. Based on the summarized results it is interpreted that diabetes biochemical factors such as insulin and glucose are highly linked with BC biomarkers such as MCP-1, HOMA-IR, leptin, resistin, and adiponectin.